2016
DOI: 10.1080/00913847.2016.1197762
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of meniscal allograft for torn discoid lateral meniscus in young women

Abstract: Meniscal allografts have been shown to reduce pain and improve function in patients with discoid lateral meniscus tears. Though more costly, meniscal allografts may be more effective than partial meniscectomy in delaying TKA in this model. Additional future long term clinical studies will provide more insight into optimal surgical options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…All included studies performed a cost-utility analysis (CUA) having quality-adjusted life years (QALYs) as outcome measurement[2636,3840], except for one, which consisted of a cost-effectiveness analysis (CEA) with outcome measured as years to total knee alloplastic (TKA) and the subsequent incremental cost-effectiveness ratio reported as cost per year to arthroplasty gained[37]. Nine of the studies performed model-based economic evaluations with input data from the best evidence available in the literature[26,29,30,32,33,3639] while the remaining seven performed economic evaluations with data from clinical trials and cohort studies[27,28,31,34,35,40].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All included studies performed a cost-utility analysis (CUA) having quality-adjusted life years (QALYs) as outcome measurement[2636,3840], except for one, which consisted of a cost-effectiveness analysis (CEA) with outcome measured as years to total knee alloplastic (TKA) and the subsequent incremental cost-effectiveness ratio reported as cost per year to arthroplasty gained[37]. Nine of the studies performed model-based economic evaluations with input data from the best evidence available in the literature[26,29,30,32,33,3639] while the remaining seven performed economic evaluations with data from clinical trials and cohort studies[27,28,31,34,35,40].…”
Section: Resultsmentioning
confidence: 99%
“…The time horizon of the studies varied from one year to lifetime. A societal perspective was adopted in eight of the studies[2729,31,36,38,39,40] while five studies adopted a healthcare perspective or third payers’ perspective such as the National Health Service (NHS)[30,32,34,35,37]. The remaining two studies did not explicitly report the actual perspective[26,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is known as a discoid cartilage, and may be more prone to injury. Ramme et al [ 37 ] compared the cost-effectiveness of MAT and partial meniscectomy in young women with torn discoid lateral meniscus and concluded that MAT was cost-effective.…”
Section: Introductionmentioning
confidence: 99%